Burst capacity and development of interaction rules for pipelines considering radial interacting corrosion defects - Idris, N.N. (Elsevier Ltd, 2021)
Pipelines failures during its service life caused by the impact of multiple corrosion defects are most probable to occur, which may induce severe consequences as compared to single defect acting alone. Interaction rules were developed for multiple defects in the longitudinal and circumferential directions previously, but the knowledge on two or more defects aligned radially is still not well understood. This paper aims at investigating new interacting limits when corrosion defects are acting both on the internal and external wall, separated by a radial spacing, SR. The studies were carried out using burst test experiments as well as numerical modelling using pipe specimens of type API 5L X42. Six colonies of radial interacting corrosion defect arrangements were tested. The paper investigates the effects of the radial interaction by means of radial limit, SRLim. It was found that increasing the defect depths of internal and external defects would highly reduce the failure pressure, Pmultiple. Depending on the orientations of the multiple defects acting radially, the failure pressure may be less or more than the case of single defect, Psingle. Thus, the failure pressure ratio of Pmultiple/Psingle should be used as a measure, with any values larger than 0.99 depict no interaction taken place among those multiple defects. From the six colonies, only two colonies showed the significance of radial interactions. The paper then suggests that when radial interaction does not presence, multiple corrosion defects acting radially may then be treated as single defect. Â© 2020 Elsevier Ltd